O Estado perante a crise do transporte aéreo: os casos de Brasil e Moçambique - Carolina Todesco; José Júlio Júnior Guambe; Thays Regina Rodrigues Pinho; Marcos Paulo Fernandes; Amilton Luiz Novaes (Confins, 2022)
This article aims to analyze governmental action in response to the air transport crisis, adopting Brazil and Mozambique as a case study, observing whether these countries followed global trends in support of companies, or if, due to specific national circumstances, they gave different responses to the sector over the years of 2020 and 2021. For this, bibliographic and documentary research was carried out. The results show that the trends pointed out for the airline sector were partially implemented in both countries. In Brazil, government financial support was provided indirectly, through actions that ensured the survival of airlines while in Mozambique, the transfer of public resources was direct.